THE EFFECT OF PHARMACY COUNSELING ON KNOWLEDGE OF SWAMEDICATION PATIENTS IN pharmacies, MOJOROTO DISTRICT, KEDIRI CITY REGION IN 2019 - Djembor Sugeng Walujo; Ephrino Ephrino; Mega Ayu Wijayanti (JOURNAL OF PHARMACY SCIENCE AND TECHNOLOGY, 2022)
Drug counseling is an interaction between pharmacist and patient or family in the form of a structured discussion to provide opportunities for the patient or the patient's family to explore and provide assistance to improve recognition, appreciation, and interpretation so that the patient or the patient's family gain determination with their capabilities in application correct medicine, including self-medication. Self-medication is an activity or act of self-medicating with drugs without a prescription in a precise and rational manner. This study aims to determine the effect of pharmacist counseling on knowledge of self-medication patients at the Mojoroto District Pharmacy, Kediri City Region. The type of research used was analytic observational with an experimental research design of one group pretest-post-test to compare the knowledge of self-medication patients before and after being given counseling. The population used is 8 pharmacies in Mojoroto sub-district. The sampling technique used is purposive sampling with inclusion and exclusion criteria. The sample used is 67 respondents. Wilcoxon Test Results Sig. 0.00 < 0.05 indicates that there is an effect of pharmacist counseling on self-medication knowledge. The results of self-medication rationality knowledge assessment showed good (85.1%), moderate (3.0%), bad (11.9%).